Experimental investigations of thin-layer drying of leaves in a heat-pump assisted tray-type batch drying chamber - Babu, A. K. (Strojniški vestnik, 2020)
The design of a batch drying chamber with multiple trays for the thin-layer drying of fragile, heat-sensitive food materials, such as edible leaves, is a challenging task. It is essential to ensure good air distribution with minimum pressure drop in all the compartments of the drying chamber to obtain uniform drying of the product. In the present work, a drying chamber that was optimized from different configurations using computational fluid dynamics (CFD) software was fabricated and tested in the heat pump dryer. The experimental investigation was carried out with an optimized configuration for the temperature range of 50 °C to 60 °C, the relative humidity range of 20 % to 12 %, and air velocities of 1.41 m/s, 2.39 m/s, and 3.24 m/s. These optimal operating conditions were chosen based on an extensive literature survey on leaf drying. It was found that the drying process took place only in the falling rate period, fully controlled by the mechanism of liquid diffusion. The effects of air velocity on the performance parameters of the dryer were studied. Calculations based on the mean average parameters of the experimental data showed that a relatively higher heat utilization factor (0.17), moisture extraction ratio (0.375 kg/h), specific moisture extraction ratio (0.1529 kg/(kWh)), coefficient of performance (4.60), drying efficiency (76.23 %) and lower specific energy consumption (1.16 kW/kg) were obtained for a moderate drying velocity of 2.39 m/s in the heat pump drying process due to higher convection mass and heat transfer effects. Drying curves were plotted for different drying conditions and discussed. The findings were in agreement with those of many earlier research studies listed in the references section. The tested drying chamber can be used for drying all kinds of leaves in a heat pump dryer.
Keywords: Amaranth leaves; batch dryer; coefficient of performance; grelno število; heat pump dryer; listi ščira; sušenje v tankih plasteh; sušilnik na toplotno črpalko; šaržni sušilnik; thin-layer drying